Infantile Cystinosis - Castro, I (2009)
Infantile cystinosis is a rare disorder which leftuntreated results in end -stage renal disease early in life. Together with dehydration and electrolyte imbalance due to renal tubular Fanconi syndrome, endstage renal disease used to be the leading cause of death in children with cystinosis. Specific therapy with cysteamine (cystine -depleting agent) has changed the course of this disease. Instead of being fatal in childhood, it can nowadays be considered a multisystemic adult disorder. The authors report a case of a child diagnosed with Fanconi syndrome at 14 months of age and infantile cystinosis at 19 months of age in whom oral cysteamine treatment led to a good outcome during childhood.